Pre university students proficiency in symbols, graphs and problem-solving and their economic achievement - Veloo, Arsaythamby; Md Ali, Ruzlan (Canadian Center of Science and Education, 2015)
The purpose of this study is to identify the level of difficulty of symbols, graphs and problem solving items in Economic achievement among pre university students.The sample comprised of 110 students from national daily secondary schools in the state of Kedah, Malaysia.The achievement test comprised of 18 items with six symbol items, six graph items and six economic problem-solving items.The findings show that item difficulty indices for symbol items, graph items, and economic problem-solving items are 0.65, 0.45, and 0.49 respectively, which indicate that students in the study can understand items presented using symbols better than the graphs or economic problem-solving items.The students faced greater difficulty with graph items compared to economic problem-solving items.For symbol items, students faced difficulty in answering Item 2 (Saving Function—0.20) and Item 4 (Market Balance—0.28). For the graph items, the students had difficulty in answering Item 4 (Demand—0.25) and Item 2 [Two sectors C + I—0.29).For the Economics problem-solving items, students found it difficult to answer Item 5 (Tax—0.21).The findings in the study imply that a combination of symbol, graph and economic problem-solving items should be taken into account when constructing items for Pre University Economics tests.